»Ich bin eine Kanackin«: Decolonizing Popfeminism – Transcultural Perspectives on Lady Bitch Ray - Tuzcu, Pinar (transcript, 2017)
Pinar Tuzcu explores rapper Lady Bitch Ray's performance and particularly her use of the term Kanackin. She combines issues of popfeminism and postmigration through speculative methodology and invites us to forget prescriptive definitions by proposing paradoxicality as a source to diversify our concepts of feminism. By means of Situational Analysis, her study works through the contradictory forms of positioning that occurred in group discussions with Turkish-German university students about Lady Bitch Ray's music videos. In this book, Tuzcu argues that these contradictory forms of positioning bear traces of emergent discourses that reach beyond Western-centric descriptions of feminism in Germany.